Напрями гармонізації ставки ПДВ в Україні в контексті міжнародних торговельних відносин - Філіппова, Н.В. (Економіка промисловості, 2016)
Запропоновано інструментарій відбору країн - торговельних партнерів України, з використанням якого розраховано варіанти гармонізованих ставок ПДВ. Створено модель оцінки впливу різних варіантів гармонізованої ставки ПДВ на надходження даного податку в бюджет України. Розроблено окремі рекомендації щодо вдосконалення нормативно-законодавчої бази України в частині інтенсифікації міжнародних торговельних відносин з урахуванням необхідності виконувати вимоги Угоди про асоціацію з ЄС. Предложен инструментарий отбора стран - торговых партнеров Украины, с использованием которого рассчитаны варианты гармонизированных ставок НДС. Создана модель оценки влияния различных вариантов гармонизированной ставки НДС на поступления данного налога в бюджет Украины. Разработаны отдельные рекомендации по совершенствованию нормативно-законодательной базы Украины в части интенсификации международных торговых отношений с учетом необходимости выполнять требования Соглашения об ассоциации с ЕС. Ukraine faces the necessity to fulfill the requirements of Association agreement between Ukraine and EU. One of them is the harmonization of the tax legislation and tax system, particularly - value added tax (VAT). This demand is due to the fact that VAT has become the tax that allowed Europe further convergence and trade intensification after border and customs control mitigation. Furthermore, revenues from this tax contribute up to 7 percent of all tax revenues to the budgets of EU member countries. That, in turn, allows national governments to perform economic, social and other programs. But the directions of harmonization (especially of tax rates) must be carefully chosen. In this sense economic and mathematical models can be useful.After conducting thorough analysis of existing models of VAT harmonization and their shortcomings the model of VAT harmonization for Ukraine has been made. It consists of several parts: 1) allocation of criteria of selection of countries that have trade relations with Ukraine; 2) selection of such countries; 3) calculation of harmonized standard VAT rate; 4) defining the influence of harmonized standard VAT rate on VAT revenues of the budget of Ukraine. According to the estimations of the influence of harmonized standard VAT rate on VAT revenues of the budget of Ukraine the recommendations on the choice of harmonized VAT rate have been made. It was noted in the paper that harmonization of VAT rate will not be sufficient for intensifying international trade and process of integration with EU. The state program of international policy, as well as improvement of political and economic situation is needed. And as for the VAT in the context of international trade relations the advancing of the automatic refund of export VAT mechanism is urgent for Ukraine.